ALTERATIONS IN ORAL MICROBIOTA AS POTENTIAL BIOMARKERS FOR AUTISM SPECTRUM DISORDER: REVIEW AND PERSPECTIVES - dos Santos, Pedro Guimarães Sampaio Trajano; da Paz, Eliana Santos Lyra; Rodrigues, Verônica Maria de Sá; de Araújo, Vanessa Lessa Cavalcanti; de Ataíde Filho, Ailton Coelho; de Almeida, Gustavo Moreira; Alves, Josué; Prosini, Priscila; de Menezes, Maria Regina Almeida; da Silva, Vânia Cavalcanti Ribeiro; Travassos, Rosana Maria Coelho; Silva, Luciano Barreto (ARACÊ, 2025)
Objective: The objective of this narrative literature review article is to address the correlation between autism spectrum disorder and oral microbiota. Methodology: This article is a narrative literature review, and a specific methodology was developed for this type of review. To develop the article within the standards of a narrative review, Rother’s (2007) study was used, which addresses systematic and narrative reviews, explaining how each type of review should be constructed, its characteristics, approach and structure, information that was useful to serve as a guide in this article. In addition, seeing the need to acquire articles with scientifically proven information that could compose the review, searches were carried out in the following online databases: COCHRANE; Scielo; PubMed; PROSPEROUS; Elsevier; The Cochrane Library in conjunction with Google Academy. In order to obtain only results that fit the topic addressed in the article, the following descriptors were used: Microbiota; Biomarkers; Autism Spectrum Disorder. Results: Recent studies have studied the bacteria present in the mouths of people with autism and people without autism, to identify differences in the microbiota. Other studies have studied oral bacteria of children with autism and neurotypical children, to identify bacteria that can be biomarkers in the diagnosis. Conclusion: Studies have obtained positive results for the scientific community, finding specific bacteria in children with ASD, which can be used as biomarkers contributing to early diagnosis. However, there is a need to expand studies on the subject to obtain more evidence so that these biomarkers become solid in the scientific community, enabling their use.